2019
DOI: 10.3390/f10100890
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Temperature Differences between Liana-Infested and Non-Liana Infested Areas in a Neotropical Dry Forest

Abstract: Lianas (woody vines) are important non-structural elements of all tropical forests. Current field observations across the Neotropics suggest that liana abundance is rising as a result of forest disturbance, increasing atmospheric CO2, and more frequent extreme climate events. Lianas can cause mechanical stress on their host trees, thus increasing mortality, in addition to potentially reducing carbon storage capacity. Furthermore, previous studies have suggested that liana leaves have an overall higher temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Our results (Figure 4 in particular) also suggest that multispectral sensors (alone or in combination with thermal cameras (Guzmán et al 2018; Yuan et al 2019) or LiDAR) should be able to detect forest stands characterized by high liana coverage. In a related study, Visser et al (2021) show how radiative transfer models can assist in the estimation of liana traits from hyperspectral images of liana-infested canopies just as it is currently achieved for trees (Gong et al 2003; Meroni et al 2004; Serbin et al 2015).…”
Section: Discussionsupporting
confidence: 62%
“…Our results (Figure 4 in particular) also suggest that multispectral sensors (alone or in combination with thermal cameras (Guzmán et al 2018; Yuan et al 2019) or LiDAR) should be able to detect forest stands characterized by high liana coverage. In a related study, Visser et al (2021) show how radiative transfer models can assist in the estimation of liana traits from hyperspectral images of liana-infested canopies just as it is currently achieved for trees (Gong et al 2003; Meroni et al 2004; Serbin et al 2015).…”
Section: Discussionsupporting
confidence: 62%
“…Lianas have been successfully detected in forest canopies and gaps by using UAVs fitted with standard cameras because of the ultra-fine resolution, down to centimetre, of the imagery obtained (Waite et al, 2019). Using visible to NIR (Li et al, 2018) and thermal sensors (Yuan et al, 2019) has also proved successful. Waite et al (2019) went beyond detecting liana presence in tree canopies, also assessing the degree of liana infestation in tree canopies.…”
Section: Current Remote Sensing Progressmentioning
confidence: 99%
“…RotorKonzept® RK-8x multicopter UAV Yuan, Laakso, Marzahn, and Sanchez-Azofeifa (2019) 1. Leica ALS50-II -8 W class 4 laser with radiation at 1064 nm recording up to four discrete returns for each emitted pulse.…”
Section: Sensor Platform Citationmentioning
confidence: 99%
“…Many studies have shown that lianas, as a plant group, can be distinguished from trees based on their spectral reflectance, particularly in the visible (400-690 nm) and Near Infrared (NIR)-region (700-1340 nm) [17][18][19][20][21], as well as thermal properties [22,23]. Subsequently, recent research has successfully detected lianas using data acquired from; UAVs, fitted with RGB [24,25] and thermal [26] sensors, satellite imagery [27] and airborne hyperspectral imagery in seasonal [28] and aseasonal forests [29]. While airborne sensors have the potential to provide high spatial and spectral resolution imagery which can be used to detect liana infestation at landscape-scales, satellite-based sensors can typically afford more frequent measurements across much larger geographical extents.…”
Section: Introductionmentioning
confidence: 99%